Taguchi optimization of process parameters in friction stir spot welding of AA5754 and AA2024 alloys - (:unkn) unknown (Trans Tech Publications Ltd, 2014)
The feasibility of friction stir spot welding was studied on AA5754-H22 and AA2024-T3 aluminum alloys which have widespread applications in aircraft and automotive industries. The quality of the joint was evaluated by examining the characteristics of the joint as a result of lapshear fracture load. Taguchi approach of the parameter design was used as a statistical design of experiment technique to set the optimal welding parameters. The experiments were arranged by using Taguchi's L9 orthogonal array. The signal-to-noise ratio and the analysis of variance were utilized to obtain the influence of the friction stir spot welding parameters on the lap-shear fracture load. Finally, the results were confirmed by further experiments. © (2014) Trans Tech Publications, Switzerland.
Keywords: Aluminium alloys; Friction stir spot welding; Process optimization; Taguchi method